Peningkatan Hasil Belajar Passing Sepak Bola Melalui Permainan Pemburu Binatang (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2015)
The purpose of this study was to determine the learning outcome approach passing through playing soccer Beast Hunter on fourth-grade students of SD Negeri Batuagung 1 Balapulang District of Tegal 2014. This study was conducted in PTK SD Negeri Batuagung 1 Balapulang District of Tegal, the samples in this study were fourth graders, amounting to 24 students. This research method is Classroom Action Research. This study uses 2 cycles. The results showed that the learning outcomes passing football played by using the approach of animals hunters have a positive impact as seen on mastery learning outcomes of students who exceed the predetermined KKM 75 has increased the mastery learning in the first cycle reaches 70.83%, while the second cycle mastery learning reaches 95.83%. It is concluded that learning football passing play tracker approach has a positive impact, which can improve learning outcomes, interest, and motivation to learn